ANALISA KARAKTERISTIK SOSIAL-EKONOMI MASYARAKAT TERHADAP EFEKTIVITAS JEMBATAN PENYEBERANGAN DI KOTA BANDA ACEH - Elfiwardah Idris; Sugiarto Sugiarto; Sofyan M. Saleh (Prodi Magister Teknik Sipil Unsyiah, 2019)
Pedestrian bridges are provided by the government to make it easier for pedestrians to cross over crowded roads. The phenomenon that occurs under the mind is used for motor crossings. Prepare the purpose of this study to determine the types of socio-economic communities for crossings in Banda Aceh City. The data retrieval method used was Stated Preference (SP) with 180 respondents taken randomly stratified (random sampling) with target of user and society respondents around pedestrian bridge. Processing and data analysis using descriptive statistics. The results of descriptive analysis of socio-economic characteristics of the public’s on the effectiveness of pedestrian bridges, the most dominant cause is the majority of male gender, aged 20-29 years old, primary, junior and senior high school, civil servant, private employee, self-employed, student, monthly income below 2 million rupiah, travel purpose for work / office, sales, cargo / freight, trader, school / college / study. Judging from the government policy in the application of pedestrian bridges, the result is that most people agree with the implementation of the pedestrian bridge in Banda Aceh City, and most respondents have also used pedestrian bridges to cross the road to the destination.